Legal traditions and constitutional interpretation of bills of rights in Africa : comparative perspectives from the Constitutional Courts of Benin, the Democratic Republic of Congo and South Africa - Fombad, Charles Manga (University of Pretoria, 2021)
Thesis (PhD)--University of Pretoria, 2021.